How do you simplify #(m^6r^5p^3)/(m^5r^2p^3)#?

1 Answer
Feb 22, 2017

Answer:

See the entire simplification process below:

Explanation:

We will use this rule for exponents to simplify this expression:

#x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))#

#(m^color(red)(6)r^color(red)(5)p^color(red)(3))/(m^color(blue)(5)r^color(blue)(2)p^color(blue)(3)) = m^(color(red)(6)-color(blue)(5))r^(color(red)(5)-color(blue)(2))p^(color(red)(3)-color(blue)(3)) = m^1r^3p^0#

Now, we will use these two rules for exponents to complete the simplification:

#a^color(red)(1) = a# and #a^color(blue)(0) = 1#

#m^color(red)(1)r^3p^color(blue)(0) = mr^3 xx 1 = mr^3#